KATA-KATA TABU DALAM BAHASA INGGRIS DAN BAHASA BIAK (SUATU ANALISIS KONTRASTIF) - Urbinas, Yubeltin; Rattu, Jultje A.J.; Lasut, Theresia M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTSThis research entitled â€œTaboo Words in English and Biak Language: A Contrastive Analysisâ€ is analyzed and described in sociolinguistic field. The objectives of this research are to identify, classify and describe the types and meaning of taboo words and to analyze their differences and similarities. This research used a descriptive method. The data are analyzed using theory of Wardhaugh (1986:230) to find out the types, using Leechâ€™s theory (1981:19) to find out the meaning, and were contrasted to find out the differences using Ladoâ€™s theory (1971:217). The significances of this research are theoretically, this research is expected to give contribution to the development of sociolinguistics especially in terms of taboo words and to practically it can be useful, for young Biak generation who want to learn taboo words in English and for foreign learners who want to study taboo words in Biak language. The result of this research shows that taboo words found in Biak language were classified into eight types, they are, sex, excretion, bodily function, death, animal, religion, and supernatural. The simillarities in English and Biak Language is the use of this word can cause misunderstanding and the differences of English and Biak Language is taboo words in Biak have levels whereas in English there is no level. This shows that the causes of using taboo words are to express the happiness, such as anger, emotion, and surprise, to joke, to insult, and to talk about sex.Â Keywords : Taboo Words; English and Biak Language; Contrastive Analysis